Earthworms affect plant growth and resistance against herbivores: A meta‐analysis. (11th September 2017) - Xiao, Zhenggao; Wang, Xie; Koricheva, Julia; Kergunteuil, Alan; Le Bayon, Renée‐Claire; Liu, Manqiang; Hu, Feng; Rasmann, Sergio
Abstract: Subterranean detritivores such as earthworms can increase soil nutrient availability through their burrowing and casting activities. A number of recent studies have explored whether these changes caused by earthworms may in turn affect plant performance and resistance to herbivores, but no formal synthesis of this literature has been conducted to date. We tested for the effects of earthworms on plant growth, resistance and chemical defences against insect herbivores by performing a meta‐analysis of the existing literature up to 2016. We also explored ecological factors that might explain among‐studies variation in the magnitude of the earthworm effects on plant growth and resistance. We found that earthworm presence increases plant growth (by 20%) and nitrogen content (by 11%). Overall, earthworms did not affect plant resistance against chewing herbivores (caterpillars, slugs and rootworms), and even led to a 22% decrease in plant resistance against phloem‐feeding herbivores (aphids). However, earthworm presence increased production of chemical defences by 31% when plants where attacked by cell‐feeders (thrips), and resulted in an 81% increase in resistance against thrips. The magnitude of earthworm effects was stronger when earthworm inoculations consisted of a mix of species and ecological types, and when densities of earthworms were high. These results suggest that earthworm presence is an important factor underlying natural variation in plant defences against herbivores, and call for a better integration of the soil fauna in the studies of plant‐herbivore interaction, both for applied and fundamental research. A plain language summary is available for this article. Abstract : Plain Language Summary